Multi-input DC/DC converters in connection with distributed generation units – A review. (December 2016) - Khosrogorji, S.; Ahmadian, M.; Torkaman, H.; Soori, S.
Abstract: In this paper, recent advances in multi-input converters are studied. In the past, some DC/DC converters used to be connected parallel to each other and thus multi-input converters were created. But today, some new structures have been proposed for this purpose. The main reason behind employing these converters is using less semiconductors, occupying less volume, thus reduction in manufacturing cost of the converters. In this article, multiple input converters are categorized into three groups: magnetic, electrical and electro-magnetic types. The first group includes topologies that have multi-winding transformer. The second group consists of topologies that have DC-link and sources connected to the DC-link and the latter includes topologies that have DC-link and two-winding transformer. In this paper, the topologies of various multi-input DC/DC converters will be reviewed and compared from different aspect such as, the battery life, the soft-switching, the source utilization, the isolation between the input and the output. The main reason for composing this paper is the collection of information about DC/DC multi-input converters. This review paper is the first of its kind with the aim of providing an information source and a selection guide on multi-input DC/DC converters for researchers, designers and application engineers.